IMPLEMENTASI MANAJEMEN PEMBELAJARAN DARING BAGI PESERTA DIDIK SEKOLAH DASAR DI PEDESAAN PADA MASA PANDEMIK COVID-19 - Luthfi Audia Pribadi, - (2021)
Pandemik Covid-19 memberikan dampak yang cukup besar dalam kehidupan masyarakat Indonesia, salah satunya dalam aspek pendidikan. Focus utama peneliti lebih kepada kesenjangan yang dialami oleh Pedesaan dalam pelaksanaan Pembelajaran berbasis Learning Management System (LMS). Masalah yang terjadi terkesan sangat kompleks, terkesan sukar di Implementasikan dan menjadi beban baru bagi Sumber Daya Manusia dalam Kegiatan Belajar Mengajar. Penelitian ini dilatarbelakangi oleh Surat Edaran Kementrian Pendidikan Dan Kebudayaan No 4 Tahun 2020 Tentang Pelaksanaan pembelajaran Jarak Jauh (PJJ) dan mengharuskan pembelajaran berbasis Dalam jaringan (Daring). Penelitian ini menggunakan pendekatan deskriptif-kualitatif yaitu menggambarkan dan mengungkapkan fakta yang ada kemudian dijelaskan secara deskriptif dengan kata-kata atau uraian. Teknik pengumpulan data yang digunakan melalui teknik wawancara, teknik observasi dan teknik menyalin atau dokumentasi. Hasil penelitian ditemukan bahwa Implementasi Manajemen Pembelajaran Daring di SDN Negla (Kertasari) meliputi: 1) Eksisting pedesaan melalui kegiatan mendeskripsikan keadaan alam yang alami dengan mengidentifikasi potensi yang di miliki. 2) Implementasi Manajemen Pembelajaran meliputi kegiatan: a). Perencanaan pembelajaran yang diantaranya adalah penyusunan RPP, mempersiapkan bahan ajar, mempersiapkan media pengajaran atau pembelajaran, b). Pengorganisasian meliputi kegiatan pembagian tugas sesuai dengan tanggung jawab dan juga menentukan alur komunikasi antara Guru, orang tua dan kepala sekolah c). Pelaksanaan pembelajaran, meliputi kegiatan pendahuluan, kegiatan inti hingga kegiatan penutup d) Evaluasi pembelajaran yang meliputi aspek Keterampilan, Sikap dan Pengetahuan. Adapun bentuk penilaian berupa penilaian penugasan (proyek), dan penilaian sikap; 3) Faktor pendukung dan Faktor penghambat selama pembelajaran di masa Pandemi COVID-19 serta; 4) Upaya yang dilakukan untuk mengatasi hambatan yaitu menciptakan inovasi pembelajaran yang sesuai dengan lingkungan pedesaan. Menganalisis kebutuhan pembelajaran, sesuai dengan kondisi eksisting pedesaan. Pembelajaran Dalam Jaringan memiliki fleksibilitas dalam pelaksanaannya dan mampu mendorong guru untuk lebih kreatif dalam mengajar selain itu siswa dituntut untuk lebih mandiri dan termotivasi untuk lebih aktif belajar. pembelajaran adalah salah satu kegiatan yang menjadi landasan pendidikan yang melahirkan Sumber Daya Manusia yang berkualitas, oleh karena itu pembelajaran yang terorganisir dan terencana dapat mencapai tujuan yang efektif dan terarah. Kata Kunci: Covid-19, Manajemen Pembelajaran Daring, Pedesaan ABSTRACT Luthfi Audia Pribadi: IMPLEMENTATION OF ONLINE LEARNING MANAGEMENT FOR PRIMARY SCHOOL STUDENTS IN THE COUNTRY DURING pandemic COVID - 19 (Research Forum In SDN Negla (Kertasari). The Covid-19 pandemic has had a considerable impact on the lives of Indonesian people, one of which is in the aspect of education. The main focus of researchers is more on the gaps experienced by rural areas in the implementation of Learning Management System-based Learning (LMS). The problems that occur seem very complex, seem difficult to implement and become a new burden for Human Resources in Teaching and Learning Activities. This research is motivated by the Circular of the Ministry of Education and Culture No. 4 of 2020 concerning the Implementation of Distance Learning (PJJ) and requires online-based learning. This study uses a descriptive-qualitative approach, namely describing and revealing existing facts and then describing them descriptively with words or descriptions. Data collection techniques used were interview techniques, observation techniques and copying or documentation techniques. The results of the study found that the implementation of online learning management at SDN Negla (Kertasari) includes: 1). Learning planning which includes the preparation of lesson plans, preparing teaching materials, preparing teaching or learning media, 2). Organizing includes the division of tasks according to responsibilities and also determines the flow of communication between teachers, parents and school principals 3). Implementation of learning, including preliminary activities, core activities to closing activities 4) Evaluation of learning which includes aspects of Skills, Attitudes and Knowledge. The form of assessment is in the form of assignment (project) assessment, and attitude assessment. 4) Supporting factors and inhibiting factors during learning during the COVID-19 Pandemic and 5) Efforts made to overcome obstacles, namely creating learning innovations that are in accordance with the rural environment. Analyzing learning needs, in accordance with the existing rural conditions. The conclusion in this study, Online Learning has flexibility in its implementation and is able to encourage teachers to be more creative in teaching besides that students are required to be more independent and motivated to be more active in learning. Learning is one of the activities that form the basis of education that gives birth to quality human resources, therefore, organized and planned learning can achieve effective and directed goals. Analyzing learning needs, in accordance with the existing rural conditions. The conclusion in this study, Online Learning has flexibility in its implementation and is able to encourage teachers to be more creative in teaching besides that students are required to be more independent and motivated to be more active in learning. Learning is one of the activities that form the basis of education that gives birth to quality human resources, therefore, organized and planned learning can achieve effective and directed goals. Analyzing learning needs, in accordance with the existing rural conditions. The conclusion in this study, Online Learning has flexibility in its implementation and is able to encourage teachers to be more creative in teaching besides that students are required to be more independent and motivated to be more active in learning. Learning is one of the activities that form the basis of education that gives birth to quality human resources, therefore, organized and planned learning can achieve effective and directed goals. Online Learning has flexibility in its implementation and is able to encourage teachers to be more creative in teaching besides that students are required to be more independent and motivated to be more active in learning. Learning is one of the activities that form the basis of education that gives birth to quality human resources, therefore, organized and planned learning can achieve effective and directed goals. Online Learning has flexibility in its implementation and is able to encourage teachers to be more creative in teaching besides that students are required to be more independent and motivated to be more active in learning. Learning is one of the activities that form the basis of education that gives birth to quality human resources, therefore, organized and planned learning can achieve effective and directed goals. Keywords: Covid-19, Online Learning Management, Rural